MacBook Air how incomplete is it?. - McCracken, Harry
The list of features missing from Apple's wafer-thin laptop is almost as long as the list of what it's got.
Keywords: Hard disks (Computer science); Ethernet (Local area network system); Random access memory; Optical drives; FireWire